Alignment of poultry sector actors with avian influenza control in Ethiopia - Kelemwork, Fassil; Belay, Berhanu; Bett, Bernard; Randolph, Thomas (International Food Policy Research Institute, 2010)
The outbreak and spread of Asian-lineage highly pathogenic avian influenza (HPAI) from Asia to Europe and Africa in 2003-2007 challenged national disease surveillance and response programs particularly in those countries where infection occurred. Ethiopia has not had the disease, but it is considered as being vulnerable because it lies under the pathway of migratory birds and has an expansive border that makes it difficult to control cross-border trade in poultry and poultry products. Some of the challenges that the country might face in preventing and controlling HPAI relate to uncertainty about the epidemiology of the disease, resource and organizational constraints, and variable compliance with HPAI control measures by actors in the poultry sector. This study characterized control measures in terms of the expected degree of compliance among actors in the value chain and the agents responsible for their implementation, and identified specific actors who may be expected to act as compliance fail-points to successful implementation of control measures.